Chromium isotope fractionation during magmatic processes: Evidence from mid-ocean ridge basalts. (15th June 2022) - Ma, Haibo; Xu, Li-Juan; Shen, Ji; Liu, Sheng-Ao; Li, Shuguang
Abstract: Chromium (Cr) isotopes represent a powerful tool for tracing the redox conditions during planetary magmatic evolution. However, so far, the systematic investigation of Cr isotope variation has been only performed on ocean island basalts (OIBs) in terrestrial magmatic rocks. Therefore, the Cr stable isotope compositions (expressed as δ 53 Cr relative to NIST SRM 979) of other magmatic rocks, formed under different oxygen fugacity, have remained unconstrained. In this paper, we present the first Cr stable isotopic data of mid-ocean ridge basalts (MORBs) from the Eastern Pacific Ocean ridge, the Indian ridge, and the Atlantic Ocean ridge. The oxygen fugacity of such basalts is different from that of the above-mentioned OIBs. The Rhyolite-MELTS model shows that the chemical composition variations in the studied basalts are induced by varying extents of fractional crystallization of olivine, clinopyroxene, plagioclase, and spinel. The δ 53 Cr values of the MORBs range from −0.27 ± 0.03‰ to −0.07 ± 0.02‰ ( n = 28), and two distinct groups of basalts are identified based on the correlation between δ 53 Cr and MgO. On the one hand, the δ 53 Cr of group I basalts (−0.27 ± 0.03‰ to −0.14 ± 0.03‰; n = 24) are systematically lower than the established average value of the Bulk Silicate Earth (BSE) (δ 53 Cr = −0.12 ± 0.04‰; 2SD), which are positively correlated with their MgO and Cr concentrations, indicating that Cr isotopes are fractionated during magmatic differentiation. Moreover, Rayleigh fractionation modelling suggests that the crystallization of olivine, clinopyroxene, and spinel gives rise to the Cr depletion and thereby decreases δ 53 Cr values. On the other hand, group II basalts (−0.10 ± 0.03‰ to −0.07 ± 0.02‰; n = 4) exhibit higher δ 53 Cr values than group I with identical MgO and Cr concentrations. This is possibly associated with the crystallization of clinopyroxene under low pressure. The average Cr isotope composition (δ 53 Cr = −0.16 ± 0.02‰, n = 3) of the primitive basalts (MgO > 9%) represents that of the primary MORB melt, which is lighter than the average value of BSE. Using the non-modal melting equations, the δ 53 Cr of the MORB mantle source is estimated to be −0.12 ± 0.02‰ (2σ), which is consistent with that of BSE. Compared with the Cr isotopic data of OIBs from Fangataufa island, we find that the equilibrium fractionation factors (Δ 53 Crcrystal-melt = +0.04‰ to +0.13‰) of MORBs during fractional crystallization are larger than that of Fangataufa island lavas (Δ 53 Crcrystal-melt = 0.010 ± 0.005‰ for low-K suite, and 0.020 ± 0.010‰ for high-K suite; Bonnand et al., 2020a), indicating that the basalts from Fangataufa island have higher oxygen fugacity than those of MORBs analyzed in this study, which is strongly supported by their higher V/Sc ratios.